Flavoprotein Protocols - Chapman, Stephen K. (Humana Press, 1999)
UV-Visible Spectroscopy as a Tool to Study Flavoproteins -- Identifying and Quantitating FAD and FMN in Simple and in Iron-Sulfur-Containing Flavoproteins -- Fluorescence Analysis of Flavoproteins -- Potentiometric Measurement of Oxidation-Reduction Potentials -- Flavoprotein Kinetics -- Application of Freeze Quenching to the Study of Rapid Reactions in Flavoproteins -- Application of Electron Spin Resonance (ESR) for Detection and Characterization of Flavoprotein Semiquinones -- Circular Dichroism Studies of Flavoproteins -- Vibrational Spectroscopy of Flavoproteins -- NMR of Flavoproteins -- Flavoprotein Resolution and Reconstitution -- Flavoenzyme Structure and Function -- Identification of Covalent Flavoproteins and Analysis of the Covalent Link -- Flavin Synthesis and Incorporation into Synthetic Peptides -- Computational Methods in Flavin Research -- Flavins and Flavoenzymes in Diagnosis and Therapy.
Keywords: Labortechnik; Flavoenzym